Spór między Komisją Europejską a rządami państw członkowskich o model reformy ustrojowej Unii Gospodarczej i Walutowej w latach 2010-2023 (Politeja, 2024)
DISPUTE BETWEEN THE EUROPEAN COMMISSION AND THE GOVERNMENTS OF MEMBER STATES OVER THE MODEL FOR THE SYSTEM REFORM OF THE ECONOMIC AND MONETARY UNION IN THE YEARS 2010-2023The primary research objective of the article is to analyze the System Reform of the Economic and Monetary Union (EMU) from 2010 to 2023 from the perspective of the dispute between the European Commission and the governments of Member States over the model of this reform. The author formulated two research hypotheses. The first one is based on the assumption that the implementation of the reform faced numerous difficulties and barriers resulting from the negative attitudes of the governments of some Eurozone member states towards the implementation of selected projects of the European Commission, but also from the accumulation of several international crises that the European Union was facing at the time. These were the migration crisis in 2015-2016 and then from 2022, the pandemic crisis in 2020-2021 and the geopolitical crisis caused by Russia’s aggression against Ukraine from 2022. The second hypothesis is that the main axis of disagreement between the Commission and the governments of Member States was the limits of financial solidarity and the target System Model of the EMU. Following this, the author formulated four research questions: (1) On which issues did the positions of the European Commission and the Eurozone Summit converge and on which issues did they diverge, and why? (2) To what extent did disagreements between Member State governments over the limits of financial solidarity and the target integration model of the EMU determine the direction of System Reform? (3) How important were the aforementioned international crises for the fate of the reform? (4) What were the main achievements and failures of the EMU System Reform?